Does it Matter What We Measure? Domain-specific Professional Knowledge of Physics Teachers - Cauet, Eva; Liepertz, Sven; Borowski, Andreas; Fischer, Hans E. (Swiss Journal of Educational Research, 2018)
Can we be confident that extensively validated tests for teachers on their professional knowledge actually measure what matters for effective teaching? This study investigated the relations between physics teachers’ domain-specific professional knowledge, students’ cognitive activation – as a measure for the quality of instruction in each of the teachers’ classrooms – and the achievement of their students using multi-level analysis. Neither teachers’ content knowledge (CK) nor their pedagogical content knowledge (PCK) correlated significantly with their support of students’ cognitive activation in the classroom; nor did their professional knowledge explain any variance of student learning gains. While these results have to be interpreted carefully for various reasons, they question in particular the validity of the PCK test, which is dealing with content accepted in the community, but normatively set. Moreover, the findings of this study emphasize the importance of connecting professional knowledge to classroom and student variables in order to prove that what tests measure matters for effective teaching.